The prevalence of neurological disorders in older people in Tanzania. (31st July 2012) - Dewhurst, F.; Dewhurst, M. J.; Gray, W. K.; Aris, E.; Orega, G.; Howlett, W.; Warren, N.; Walker, R. W.
<x xml:space="preserve">Abstract</x> Objectives There are few data on neurological disorders prevalence from low‐ and middle‐income countries, particularly sub‐Saharan Africa (SSA) and none specific to the African elderly. We aimed to determined the prevalence of neurological disorders in those aged 70 years and over in a rural African community. Materials and methods This study was a cross‐sectional two‐phased community epidemiological survey set in the rural Hai district of Tanzania. Screening was performed with a validated screening questionnaire with high sensitivity and specificity. Positive responders to screening underwent full neurological history and examination to confirm or refute the presence of neurological disorders and to classify the disorder using the International Statistical Classification of Diseases and Related Health Problems 10th Revision (ICD‐10). Results Of 2232 participants, there were 384 neurological diagnoses amongst 349 people. The age‐adjusted prevalence of people with neurological diagnoses was 154.1 per 1000 (95% CI 139.2–169.1). The age‐adjusted prevalence per 1000 of the most common neurological disorders were tremor (48.2), headache (41.8), stroke (23.0), peripheral polyneuropathy (18.6), upper limb mononeuropathy (6.5) and parkinsonism (5.9). Conclusions This is the first published community‐based neurological disorders prevalence study specifically in the elderly in SSA. It reveals a high prevalence of neurological morbidity and demonstrates the contribution neurological disorders make to the non‐communicable disease epidemic. This is likely to increase as the population of low‐income countries ages constituting a public health dilemma.